INSPECTION IN THE FIELD OF EMPLOYMENT RELATIONSHIPS AND PENALTY PROVISIONS UNDER THE LABOR LAW - Belovski, Vojo (Journal of process management and new technologies, 2017)
If the primary efficacy of the projected normative order is absent, the mechanism of secondary efficacy occurs, which implies forceful realization of norms – repressive measures, i.e. coercive measures, and punitive undertakings. In the Labor Law there is a whole Chapter (Chapter XXV) devoted to inspection supervision in the field of employment relationships. Labor inspection functions as a specialized organ of the Ministry which is responsible for the affairs in the area of labor. A request for a control by a labor inspectorate can be instigated by a worker individually, by the Trade Union and by the employer. It can also be instigated ex officio by the inspection supervision. Concerning supervision of the legal commencement of employment the procedure for the labor inspector is as follows: a) to find employees at the place of work of the employer who are not employed according to the law; b) employees not registered in the mandatory social insurance; c) shall make a decision and shall order the employer to commence employment with the persons found there or with other persons without public job announcement within 8 days; d) to employ for an indefinite period of time; e) the number of employees shall not be reduced within the next three months; f) will make a proposal for settlement by issuing a payment order of misdemeanor for the person responsible or a person authorized by the employer under the Law on Misdemeanors; g) if the employer does not accept the payment order of misdemeanor, the inspector in charge will file a request for initiating a misdemeanor procedure. As an example of the misdemeanor provisions, a fine of 7,000 Euros in denar equivalent shall be pronounced on the employer-legal entity if: 1) if no agreement for employment has been made between the employee and the employer and the employer failed to register the employee in the Mandatory pension and Disability Insurance Fund, Health insurance and insurance in case of unemployment before the employee starts with the employment (Article 13, paragraph (1), (2) (3) and (7) of the Labor Law